Implementation Analysis Of Isak 35 In Financial Reporting Of The Gmit Church In Indonesia - Linda Lomi Ga; Yohana Febiani Angi; Siprianus G. Tefa (Eduvest - Journal of Universal Studies, 2021)
The church as a non-profit organization also deals with financial management because it gets resources to carry out its operations in the form of donations from the congregation and donors. Therefore, the church needs to implement good financial management through financial reporting according to the Interpretation of Financial Accounting Standards (ISAK) No. 35. in financial management so as to provide accurate information on financial position, performance, and cash flows as material for evaluation and making appropriate decisions. Through a joint decision with the GMIT Churches in Indonesia in the annual synod meeting, it has been recommended to carry out financial reporting according to applicable standards, but in the realization the implementation is still in the stage of revamping and preparing Human Resources as managers and readiness of financial data information. This study aims to analyze the implementation of ISAK 35 in financial reporting at the GMIT church in Indonesia. The method used is qualitative descriptive analysis. The result of the research is that GMIT churches in Indonesia have not implemented financial reporting according to ISAK Standard No. 35 because the church is still in the process of administrative reform and updating of church asset data and the church has limited human resources for managing church finances. By conducting training in the form of socialization and the practice of preparing financial reports, it will help the church overcome church problems and obstacles in carrying out financial reporting according to financial standards.